Pneumococcal vaccination in patients with systemic lupus erythematosus: A multicenter placebo-controlled randomized double-blind study. Issue 37 (5th September 2017) - Grabar, Sophie; Groh, Matthieu; Bahuaud, Mathilde; Le Guern, Véronique; Costedoat-Chalumeau, Nathalie; Mathian, Alexis; Hanslik, Thomas; Guillevin, Loïc; Batteux, Frédéric; Launay, Odile; ,
Highlights: Pneumococcal vaccination with the 7-valent PnCj vaccine is safe. There was no clear superiority of the PnCj-PPS group over the placebo-PPS group. More than 40% of patients failed to mount memory immune responses at week 52. New vaccines and/or innovative schedule designs are warranted. Abstract: Background: Invasive pneumococcal disease and respiratory tract infections are both frequent and severe in patients with systemic lupus erythematosus (SLE). This study aimed to compare the immunological efficacy and safety of pneumococcal vaccination with the 23-valent polysaccharide (PPS) vaccine alone to a sequential immunization with the 7-valent pneumococcal conjugate (PnCj) vaccine followed by PPS in patients with SLE and stable diseaase. Methods: Multicenter randomized placebo-controlled double-blind trial: PPS vaccine alone (placebo-PPS group) or PnCj vaccine followed by PPS vaccine (PnCj-PPS group) 24 weeks later. The primary endpoint was the rate of responders at week 28 to at least 5 of the 7 serotypes (4, 6B, 9V, 14, 18C, 19F and 23F) shared by both PPS and PnCj. Pneumococcal IgG antibodies' opsonophagocytic activity (OPA) were also assessed. Results: Twenty-five patients in the placebo-PPS group and 17 in the PnCj-PPS group were included in a modified intention-to-treat analysis. The primary endpoint was reached in 72% (18/25) in the placebo-PPS and 76% (13/17) in the PnCj-PPS group (p = 0.75). There was no difference in the rates of responders with OPA. At week 52, 13/18 (72%) patients in the placebo-PPS group and 10/13 (77%) patients in the PnCj-PPS group (p = 0.77) that met the primary endpoint at week 28 were still responders to ≥5/7 serotypes shared by both PPS and PnCj vaccines. Nine SLE flares were reported in 6 patients (4 in the placebo-PPS and 2 in the PnCj-PPS groups respectively, p = 0.70). Conclusion: Sequential administration of PnCj vaccine followed by PPS vaccine is safe and shows short-term immunological efficacy in patients with SLE but was not superior to the PPS vaccine alone. Trial registration: www.clinicaltrials.gov, NCTNCT00611663